Analisis Faktor-Faktor yang Mempengaruhi Produktivitas Kerja Pada Karyawan Tetap di BMT Mandiri Abadi Syariah - Yusril Ihza Harefa; Salman Nasution (Al-Sharf: Jurnal Ekonomi Islam, 2023)
This study aims to determine whether age, gender, level of education affect employee work productivity. This research was conducted at BMT Mandiri Abadi Syariah. This study uses quantitative research methods. The type of research use is survey research. The sample in this study were employees at BMT Mandiri Abadi Syariah as many as 30 people who were selected using a saturated sampling technique where all members of the population were sampled. The research instrument that will be used in this study is a questionnaire. In this study, data analysis was carried out descriptively and multiple linear regression analysis.